Multisystem Inflammatory Syndrome in Children (MIS-C) associated with Kawasaki Disease in a three-year-old girl with SARS-CoV-2 infection - Yousefi, Koroush; Poorbarat, Salar; Hoseinzadeh, Amin; Rahimi, Sajad; Abbasi, Zohreh (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2020)
Kawasaki Disease (KD) is an acute and restrictive vasculitis. Studies have noted a viral association with the occurrence of this syndrome. This article reports a child with several severe inflammatory syndrome symptoms associated with COVID-19 and KD. The patient, a three-year-old Iranian Kurdish girl without a history of internal diseases and with no history of drug and food allergies, was referred to Imam Hasan hospital three days after diarrhea, nausea, and pain in the inner part of the left thigh. Scattered rashes around the face, neck, and arms during fever were significant. Reverse transcription polymerase chain reaction (RT-PCR) was positive for COVID-19, but the lung high-resolution computed tomography (HRCT) did not show involvement, so the diagnosis of KD associated with viral infection was suggested. In further studies, Wright and 2ME tests, Widal, and purified protein derivative (PPD) tests were declared negative. After intravenous immunoglobulin (IVIG), the patient’s fever continued, but other symptoms improved. Since COVID-19 is a new disease and our understanding of its numerous symptoms is evolving, we recommend physicians to be vigilant about secondary inflammatory syndromes that induce KD; rapid treatment with IVIG and steroids may improve patients’ conditions.